New Quinoxaline Derivatives as Dual Pim-1/2 Kinase Inhibitors: Design, Synthesis and Biological Evaluation - Bruno Oyallon; Marie Brachet-Botineau; Cédric Logé; Thomas Robert; Stéphane Bach; Sajida Ibrahim; William Raoul; Cécile Croix; Pascal Berthelot; Jean Guillon; Noël Pinaud; Fabrice Gouilleux; et al. (Molecules, 2021)
Proviral integration site for Moloney murine leukemia virus (Pim)-1/2 kinase overexpression has been identified in a variety of hematologic (e.g., multiple myeloma or acute myeloid leukemia (AML)) and solid (e.g., colorectal carcinoma) tumors, playing a key role in cancer progression, metastasis, and drug resistance, and is linked to poor prognosis. These kinases are thus considered interesting targets in oncology. We report herein the design, synthesis, structure–activity relationships (SAR) and in vitro evaluations of new quinoxaline derivatives, acting as dual Pim1/2 inhibitors. Two lead compounds (5c and 5e) were then identified, as potent submicromolar Pim-1 and Pim-2 inhibitors. These molecules were also able to inhibit the growth of the two human cell lines, MV4-11 (AML) and HCT-116 (colorectal carcinoma), expressing high endogenous levels of Pim-1/2 kinases.